Kemampuan Membaca Kritis dalam Kurikulum Pendidikan di Turki dan Indonesia: Sebuah Analisis Perbandingan - Yulia Rizki Ramadhani; Azwar Ananda; Nurhizrah Gistituati; Rusdinal Rusdinal; Yuswin Harputra (JURNAL EDUCATION AND DEVELOPMENT, 2024)
This study compares the Turkish and Indonesian education curricula regarding critical reading skills. Critical reading is important for understanding and evaluating texts critically, rationally, and reflectively. In this study, data was collected from both countries to compare their critical reading skills using the comparative descriptive method. The Turkish Language Curriculum (TLCC) has a teaching hierarchy that allows for gradually developing reading skills according to grade level. The focus is on higher-order thinking skills such as classifying, interpreting, critiquing, and evaluating texts. TLCC teaches reading strategies, identifying main ideas, and evaluating media texts. In Indonesia, the Merdeka Curriculum emphasizes critical and creative thinking in reading learning. The approach is student-centered and actively engages students in the learning process. It also focuses on developing creativity, scientific reasoning, reflection, and applying Pancasila values. In conclusion, TLCC provides a gradual teaching structure and focuses on higher-order thinking skills, while the Merdeka Curriculum in Indonesia encourages critical and creative thinking in broader learning. It is recommended to improve student feedback, use diverse reading materials, and integrate concrete steps in developing reading skills with critical and creative thinking.